Mitochondrial DNA genetic diversity in six Italian donkey breeds (Equus asinus). (3rd April 2018) - Cozzi, Maria Cristina; Valiati, Paolo; Cherchi, Raffaele; Gorla, Erica; Prinsen, Raphaelle Teresa Matilde Maria; Longeri, Maria; Bagnato, Alessandro; Strillacci, Maria Giuseppina
Abstract: Donkeys have played an important role in agricultural land practices and in human historical periods of recent past and, still today, are used as a working power in several world areas. The objective of this study was to identify genetic variability in six Italian donkey breeds using mtDNA D-loop. Fifteen haplotypes, grouped in three haplogroups, were identified. The genetic indices were informative and showed a high population genetic variability. The results of AMOVA analyses based on geographic structuring of Italian populations highlighted that the majority of the observed variance is due to differences among samples within breeds. Comparison among Italian haplotypes and mtDNA D-loop sequences belonging to European domestic and Ethiopian donkeys and wild asses, clearly define two clades referred to Nubian lineage. The results can be useful to complement safeguard planes for donkey breeds that are considered to extinction endangered.